End-stage renal disease after sarcoma therapy - case 3/2014 - Baumann, D.; Amann, Kerstin Ute; Schlatter, E.; Ciarimboli, G.; Kopp, H. G.; Müller, M.; Kluba, T.; Bakos, G.; Steinke, I.; Bunz, H.; Weyrich, P.; Artunc, F. (Deutsche Medizinische Wochenschrift, 2014)
A 67-year-old male patient developed progressive renal failure following successful treatment of a soft tissue sarcoma that comprised surgical resection after neoadjuvant radiochemotherapy with the application of doxorubicin (cumulative dose 180 mg/m²) and ifosfamide (cumulative dose 33 g/m²).Plasma creatinine concentration was elevated to 4.5 mg/dl. Upon detection of glucosuria and ?1-microglobulinuria renal biopsy was performed.Histologic analysis revealed massively injured tubules that could be explained by a toxic effect of ifosfamide. Glomeruli were not affected and appeared normal. After two months of conservative therapy, the patient developed an uremic syndrome requiring hemodialysis. Ever since kidney function did not recover albeit preserved diuresis.Ifosfamide can cause end-stage renal disease by a tubulotoxic effect that may be the result of a selective intracellular uptake into the proximal tubule via the human organic cation transporter 2 (OCT2).
EVALuna2:25473